“They Give you a bus Ticket and They Kick you Loose”: A Qualitative Analysis of Post-Release Experiences among Recently Incarcerated Women Living with HIV in Metro Vancouver, Canada - Erickson, Margaret (Violence against women, 2024)
To explore the transition from correctional facilities to community among women living with HIV in Vancouver, Canada, we interviewed 19 recently incarcerated women and 6 service providers. Findings highlighted heightened risk of violence at release, a lack of immediate supports, challenges accessing safe housing and addictions treatment, and interruptions in HIV treatment and care. In the face of structural barriers, women blamed themselves for not being able to break the cycle of incarceration. There is a critical need for enhanced pre-release planning with a priority on housing and substance use services, alongside supports that are trauma-and violence-informed and culturally safe.